2012
DOI: 10.1186/1471-2318-12-46
|View full text |Cite
|
Sign up to set email alerts
|

Frail elderly patients’ experiences of information on medication. A qualitative study

Abstract: BackgroundOlder patients generally have only poor knowledge about their medicines. Knowledge is important for good adherence and for participating in decisions about treatment. Patients are entitled to be informed on an individual and adequate level. The aim of the study was to explore frail elderly patients’ experiences of receiving information about their medications and their views on how the information should best be given.MethodsThe study was qualitative in design and was carried out in 2011. Twelve frai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
79
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(92 citation statements)
references
References 24 publications
5
79
1
6
Order By: Relevance
“…(26,27) Similar to a previous Swedish study (28), the majority of our participants (94%) had strong beliefs in their benefits, however, approximately one-third of participants had strong concerns. For the majority, belief in necessity outweighed any concerns, similar to patterns observed in a frail elderly population.…”
Section: Comparison With Existing Literaturesupporting
confidence: 65%
See 1 more Smart Citation
“…(26,27) Similar to a previous Swedish study (28), the majority of our participants (94%) had strong beliefs in their benefits, however, approximately one-third of participants had strong concerns. For the majority, belief in necessity outweighed any concerns, similar to patterns observed in a frail elderly population.…”
Section: Comparison With Existing Literaturesupporting
confidence: 65%
“…At the same time however, some participants reported poor knowledge of their medications, a common trait among patients taking multiple drugs, and older people in general tend to have poorer health literacy. (28,33,34) This highlights the complex interplay of strong beliefs in the context of limited knowledge. Indeed, a previous study involving frail older patients found no relationship between strong beliefs and medication knowledge.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Continuity with an available, approachable GP is particularly valued by older patients. 59,60 Perceptions of the doctor's competence, listening skills 61 and holistic approach, 62 are all known to affect trust. 4 Perceptions of being given enough time 28,59,63 appeared strongly associated with trust and patient involvement for the most older participants.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…59,60 Perceptions of the doctor's competence, listening skills 61 and holistic approach, 62 are all known to affect trust. 4 Perceptions of being given enough time 28,59,63 appeared strongly associated with trust and patient involvement for the most older participants. The influence of societal factors on patients' perceptions of access, 64 and on trust in an individual practitioner, 2 was particularly apparent for the present participants, who have lived through cultural change.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…qualitative study by Modig et al (2012), frail elderly were comfortable with information when they trusted the physician or the information they received. They felt comfortable with information when they were satisfied with the information about their medicines and felt in control of them.…”
mentioning
confidence: 99%